Experimental and numerical cyclic response of mixed steel-concrete shear walls - Quishpe-Otacoma, Carlos; Tello-Ayala, Ken; Málaga-Chuquitaype, Christian; García-Troncoso, Natividad (Frontiers in Built Environment, 2024)
This paper examines the influence of connection detailing on the cyclic behavior of steel-concrete shear walls. To this end, experimental and numerical studies are conducted on two steel-concrete walls with identical flexural-compression diagrams but different construction methods and connection detailing. The first wall is characterized by transverse reinforcement anchored in the concrete columns along with connectors welded to the steel elements. In contrast, the second specimen incorporates transverse reinforcement directly welded to the columns and uses double the number of connectors used in the first specimen. The experimental set-up, material characteristics and construction details are described first. This is followed by a detailed account of the experimental results and observations. The experimental results are complemented with advanced Finite Element (FE) simulations to gain insight and understanding on the behavior of steel-concrete shear walls. The data presented in this paper provides valuable information for the development of mixed steel-concrete walls. A number of design improvements and practical implications are drawn from the results. It is demonstrated that the use of straight connectors between edge columns and the reinforced concrete core significantly reduces joint cracking compared to curved connectors.